Program NTC učenja na področju gibalnih dejavnosti predšolskih otrok - Polc, Urška (Šport (Ljubljana), 2020)
The article introduces pedagogical approach working with young children called NTC method of learning (NTC - Nikola Tesla Center). It consists various games for children, based on the knowledge of the development and functioning of the brain, which, according to various studies, have a particularly favourable effect on the formation and consolidation of brain connections during the most intense development, from birth to about ten years of age. The author of the NTC program Rajović emphasizes the importance of encouraging children to do activities such as various rotations, balance development exercises, dynamic eye adjustment exercises (ball activities), fine motor skills, etc. We also presented a study (Polc, 2019) that tested a sample of 4-6 year old children to test the effectiveness of the NTC method in developing the movement skills of pre-schoolers.
Keywords: brain function; delovanje možganov; gibalne sposobnosti; gibalni razvoj; igra; motor skills; NTC learning; play; predšolski otroci; preschool children; program NTC; sport; šport